Cochrane Database of Systematic Reviews 2001
DOI: 10.1002/14651858.cd001233
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical methods for induction of labour

Abstract: Analysis 39.4. Comparison 39 Any mechanical method and oxytocin versus low dose misoprostol alone: all women (not prespecified), Outcome 4 Serious neonatal morbidity/perinatal death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
95
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 39 publications
1
95
1
5
Order By: Relevance
“…The use of these methods, as compared with the use of prostaglandins, was associated with fewer episodes of excessive uterine contractions, without modifications of the risk of caesarean section. 6 In our institution, two commonly used methods of cervical ripening are vaginal misoprostol and a transcervical Foley catheter. There are a number of randomised studies comparing these two methods, most of which were published subsequent to the 2001 Cochrane review.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these methods, as compared with the use of prostaglandins, was associated with fewer episodes of excessive uterine contractions, without modifications of the risk of caesarean section. 6 In our institution, two commonly used methods of cervical ripening are vaginal misoprostol and a transcervical Foley catheter. There are a number of randomised studies comparing these two methods, most of which were published subsequent to the 2001 Cochrane review.…”
Section: Introductionmentioning
confidence: 99%
“…hole of the cervix. [8][9] Many studies compared the effects of Foley catheter with the effect of prostaglandin on cervical ripening before induction of labor and showed that the impact of the Foley catheter is better than effect of prostaglandin. [9][10][11] The purpose of this study was to compare the effect of traction on the cervix with a Foley catheter association with oxytocin and oxytocin singly, when the cervix is not appropriate to labor.…”
Section: Introductionmentioning
confidence: 99%
“…It does seem to be clear, however, that the risk of uterine hyperstimulation is lower than with prostaglandins and that their use is not associated with a significant increase in the risk of uterine rupture compared to spontaneous delivery [5]. Further, cervical stimulation with a mechanical device seems to be more effective than labour induction with oxytocin [6].…”
Section: Introductionmentioning
confidence: 99%